Comparative Study of Angle of Inclination and Neck Length of Dry Femur - Rakesh Kumar Adhikari; Binita Yadav; Subodh Kumar Yadav; Arun Chandra Singh (Journal of Nobel Medical College, 2017)
Background : The angle of inclination of the femur is the angle formed between long axis of neck of femur and long axis of the shaft of femur. The average angle of inclination (neck–shaft angle) is 126°, ranging from 115° to 140° in the adult population. As with the angle of inclination of the humerus, the angle of inclination of the femur varies among individuals and also from side to side. The aim of this study was to determine the Angle of inclination and neck length of Femur.